The Role of Muhammadiyah in Social Community - Arief Syamsuddin Muhammad Olii; Rahmawati Caco; Ibnu Rawandhy N.Hula (Green Publisher Indonesia, 2021)
Muhammadiyah is a religious organization that always adheres to the leadership under Amar ma'ruf Nahi Munkar which has been proven by always playing an active role in community empowerment, both in terms of education, religion, health, economy and other social communities. The purpose of this research is to get an idea of how the role of Muhammadiyah in Community Empowerment. In this study using a qualitative descriptive approach, the data collected later through observation, documentation and interviews. From the results of the discussion, it can be concluded that Muhammadiyah is an Islamic da'wah movement that has a commitment to purify and maintain the purity of Islamic teachings. Muhammadiyah understands that culture is thought, work and life appreciation which is a reflection of Muslims on the teachings of their religion, which is rooted in the authenticity of Islamic teachings.